A Business Model for 17SunsAgr - Koko, Tumelo Abbey (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2015)
Business Design for 17SunsAgri, an agricultural business, includes the design of the business in its entirety, starting from the business’s strategy down to its operating model at a high level.